THE ADDRESS TERMS OF BUGIS LANGUAGE IN KOMBA-KOMBA VILLAGE KABANGKA DISTRICT MUNA REGENCY - Asriani, Asriani; Aderlaepe, Aderlaepe; Nggawu, La Ode (Universitas Halu Oleo, 2020)
The objective of this study this research is to describe the forms of the address term of Bugis language In Komba-Komba Village Kabangka District Muna Regency. The method used in this research is descriptive qualitative analysis by using some techniques of collecting data such as: 1) Observation, 2) Elicitation, 3) Recording and 4) Noting. After the data being collected, the researcher analyze the following steps: 1) Transcript the data, 2) Making classification of gather data relating to greeting term, 3) Making description for last generalization objectively based on the script of data found in the field of the research. Data analysis in this research was analyzed by a functional grammar approach (Halliday, 1985) namely Field, Tenor, and Mode. The scope of this research is limited by the use of address term of Bugis language which is used in the circle of the family according to society that occurred in the formal and informal situation. The result of this research showed the address terms of Bugis language has three forms of the address term namely: 1) Address terms in Family 2) Address terms in Community 3) Address terms based on position (noble).